Vaginal Microbiome and Its Relationship with Assisted Reproduction: A Systematic Review and Meta-Analysis - Samama, Marise; Ueno, Joji; de Arruda Veiga, Eduardo Carvalho; Piscopo, Rita C. C. P.; Ikeda, Fabio; de Lemos, Nina Pires; Bidinotto, Lucas Tadeu; Silva, Márcia Guimarães da [UNESP]; Di Bella, Zsuzsanna Jarmy; Entezami, Frida (MDPI, 2025)
Background: The vaginal microbiome is an important factor influencing clinical outcomes in women undergoing assisted reproductive techniques. Objective: Our review aimed to confirm that women with a favorable vaginal microbiome have better reproductive outcomes than women who have an unfavorable vaginal microbiome. Methods: This systematic review and meta-analysis included articles published in the last 10 years, identified through keyword searches in PubMed and MEDLINE using the MeSH terms "vaginal microbiome," "reproduction," and "human reproduction." The search yielded 1735 records. Participants were categorized into women with a favorable microbiome and those with an unfavorable microbiome. To refine the taxonomic resolution at the species level, we additionally performed a bioinformatic analysis of a cohort of 56 women using multivariable association with linear models (MaAsLin2). Results: Women with a favorable microbiome had higher pregnancy rates compared to those with a less favorable microbiome (p = 0.0001, I2 = 0%, RR: 1.59). Live birth rates were also significantly higher in the favorable microbiome group than in the unfavorable microbiome group (p = 0.004, I2 = 0%, RR:1.41), with no evidence of heterogeneity. Women with an unfavorable microbiome had more miscarriages than women with a favorable microbiome (p = 0.04, I2 = 0%, RR: 0.65). Bioinformatic analysis showed that a high relative abundance of Lactobacillus crispatus increased the likelihood of pregnancy approximately sixfold. Conclusions: The favorable microbiome group, particularly participants with a high relative abundance of Lactobacillus crispatus, demonstrated better reproductive outcomes, with a higher clinical pregnancy rate, a higher live birth rate, and a lower rate of pregnancy loss, although there was a low-quality bias.